2019
DOI: 10.1007/978-3-030-30611-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Modelling with Non-stratified Chain Event Graphs

Abstract: Chain Event Graphs (CEGs) are a recent probabilistic graphical modelling tool that have proved successful in modelling scenarios with context-specific independencies. Although the theory underlying CEGs supports appropriate representation of structural zeroes, the literature so far does not provide an adaptation of the vanilla CEG methods for a real-world application presenting structural zeroes also known as the non-stratified CEG class. To illustrate these methods, we present a non-stratified CEG representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The fifth dataset is from the Christchurch Health and Development Study (CHDS) conducted at the University of Otago, New Zealand (see Fergusson et al (1986)) and the last two are simulated datasets which have structural zeros. It has been shown that the last three datasets also exhibit context-specific conditional independences (Collazo et al, 2018;Shenvi et al, 2018;Shenvi and Smith, 2019). Table 1 2 gives for each dataset the number of situations in the staged tree output by the AHC algorithm (|S (S)|), the maximum depth of the staged tree (m) and the time taken (in milliseconds) by the two compacting algorithms (T Baseline and T Optimal ) as well as the number of positions in the resulting CEG found by the two algorithms ( V(C Baseline) and V(C Optimal) ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fifth dataset is from the Christchurch Health and Development Study (CHDS) conducted at the University of Otago, New Zealand (see Fergusson et al (1986)) and the last two are simulated datasets which have structural zeros. It has been shown that the last three datasets also exhibit context-specific conditional independences (Collazo et al, 2018;Shenvi et al, 2018;Shenvi and Smith, 2019). Table 1 2 gives for each dataset the number of situations in the staged tree output by the AHC algorithm (|S (S)|), the maximum depth of the staged tree (m) and the time taken (in milliseconds) by the two compacting algorithms (T Baseline and T Optimal ) as well as the number of positions in the resulting CEG found by the two algorithms ( V(C Baseline) and V(C Optimal) ).…”
Section: Methodsmentioning
confidence: 99%
“…Non-stratified CEGs provide a truer representation of a wide range of processes containing structural zeroes (see e.g. Shenvi et al (2018); Shenvi and Smith (2019)).…”
Section: Notation and Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we have a non-stratified CEG example based on simulated falls data for 1000 individuals aged over 65. Although simulated, this data was carefully constructed to be calibrated to the various studies of falls in the elderly [Shenvi et al, 2018].…”
Section: The Datasetmentioning
confidence: 99%